THE CHRONOTOPE OF KOSOVO AND METOHIJA IN THE REPORTAGE WRITINGS OF LAZAR VUČKOVIĆ: TRANSIENCE AS A KEY THEMATIC LAYER (Heritage, 2026)
The subject of the research is directed toward the analysis of the motif of transience in the reportage texts of Lazar Vučković through the theory of the chronotope. The focus is on reportage as a hybrid genre that combines documentary factuality and literary-artistic treatment, which allows for an examination of the way this corpus functions as a specific testimony of cultural identity. The paper sheds light on the manner in which Vučković’s text literarily shapes the transient aspects of social and historical reality, transforming them into enduring records. The aim of this research is reflected in proving the thesis that these texts, grounded in pronounced subjectivity, transcend their primary informative function and develop into a quiet confession of a world that is disappearing. This opens space for a deeper understanding of the cultural, existential, and historical dimensions of Kosovo and Metohija in the mid-twentieth century.
Keywords: Lazar Vučković, reportage, chronotope, transience, Kosovo and Metohija.